Empty interculturality: the right to intercultural health of indigenous peoples and migrants in Chile - Galdámez Zelada, Liliana; Millaleo Hernández, Salvador (Acta Bioethica, 2022)
This work analyzes the development of the intercultural perspective in the protection and guarantee of the right to health in indigenous peoples and migrant population in Chile from the legal point of view. It reviews the prevalent practices and experiences in the field of public health in Chile, to establish the shape and scope of interculturality in the protection of the right to health, and the way in which it contributes to interculturality. The intercultural perspective on access to justice in Chile is weak, formal, these are incipient initiatives in the case of indigenous peoples while in the case of migrants, they hardly address language barriers.